(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Ischemic heart disease (IHD) remains one of the leading causes of morbidity and mortality worldwide, particularly among elderly patients. In recent years, increasing attention has been paid to the interaction between cardiac and renal dysfunction, known as cardiorenal syndrome, especially in patients with arrhythmias.